Estudo do perfil químico de Cyperus rotundus e avaliação do seu potencial de absorção de metais - Souza, Poliana Pereira de (2016)
The following work describes the comparative study of the variation between chemical profiles of plants of the Cyperus rotundus species – where one was collected at Vale S.A.’s dumping ground in Canaã dos Carajás city, Sossego Mine (an area contaminated by heavy metals), and compared with another of the same species collected at an adjacent area (noncontaminated by heavy metals) – through the development of analytical methods such as HPLC-UV, NMR, LC-UVSPE-NMR, LC-MS/MS, as well as through the use of chemometric tools (PCA). Statistical methodologies and chemometric analyses associated with data generated by NMR allowed, through fingerprint profiles, the discrimination between the contaminated and non-contaminated plants and the characterization of some compounds that contributed significantly to such discrimination. ICP-AES analyses were also made, in order to determine metal concentrations in different plant tissues. When analyzing the variation between chemical profiles of plants of the Cyperus rotundus species through fingerprints and data obtained from HPLC-UV-SPE-NMR and LC-MS/MS, it was possible to detect variations regarding mainly phenylpropanoid acids, fatty acids, carbohydrates and aromatic compounds, among others, which were found sometimes in the contaminated plant, sometimes in the non-contaminated plant, sometimes in both, although at different concentrations. It was also observed that in most samples spectra showed much more intense and well-defined peaks for the contaminated, thus highlighting that these compounds can be involved in the defense mechanism of the plant in a situation of oxidative stress caused by metal contamination. The results of the metal determination analyzes by ICP-AES showed much higher concentrations of the Cu element in the vegetative aerial parts of contaminated plants (921 mg/kg) in relation to the non-contaminated (3.7 mg/kg), due to this metal being the main resulting product of the local mining site. It was found that practically all metal concentrations are considerably larger in the contaminated plants when compared with the non-contaminated, therefore suggesting the hyperaccumulating behavior of the Cyperus rotundus species